Hidradenocarcinoma of scalp: a case report and review of literature - Gandla, Sowjanya; Chatterjee, Satakshi; Patil, Ashuthosh; Rao, Vishal (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Hidradenocarcinoma of the scalp is a rare skin adnexal tumour accounting for less than 0.001% of all tumors. In this study, we describe a rare presentation of the hidradenocarcinoma of the scalp in a 64 years old man. Patient presented with a right side scalp lesion in the occipital area, for which biopsy was done which showed hidradenocarcinoma. Patient underwent wide local excision of the posterior scalp lesion and posterolateral neck dissection and the patient was advised to receive adjuvant chemotherapy and radiotherapy, but the patient refused to undergo adjuvant therapy. Six months postsurgery patient had local recurrence in the posterior margin resection area and lung metastasis, which could have been prevented by adjuvant therapy. Malignant hidradenocarcinoma is a rare aggressive malignant tumour. Patients with this tumour should undergo surgical excision followed by adjuvant therapy.